2018
DOI: 10.3390/molecules23092271
|View full text |Cite
|
Sign up to set email alerts
|

Novel Riboflavin-Inspired Conjugated Bio-Organic Semiconductors

Abstract: Flavins are known to be extremely versatile, thus enabling routes to innumerable modifications in order to obtain desired properties. Thus, in the present paper, the group of bio-inspired conjugated materials based on the alloxazine core is synthetized using two efficient novel synthetic approaches providing relatively high reaction yields. The comprehensive characterization of the materials, in order to evaluate the properties and application potential, has shown that the modification of the initial alloxazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 66 publications
1
22
0
1
Order By: Relevance
“…A similar trend was also observed for progressively expanded N10-butyl substituted flavins [43]. Moreover, the studied materials provided high thermal stability reaching up to 443 • C [42]. The synthesized flavins were proposed as possible promising materials for biomimetic energy storage or photocatalytic oxygen evolution due to their tunable optical and electronic properties.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…A similar trend was also observed for progressively expanded N10-butyl substituted flavins [43]. Moreover, the studied materials provided high thermal stability reaching up to 443 • C [42]. The synthesized flavins were proposed as possible promising materials for biomimetic energy storage or photocatalytic oxygen evolution due to their tunable optical and electronic properties.…”
Section: Introductionsupporting
confidence: 75%
“…A strong dependence of the frontier molecular orbitals (FMO) energies determined by cyclic voltammetry on the size of the fused π-conjugated system was observed. The LUMO energies increased with enlarging of the π-system, while they remained virtually invariable for the non-fused flavin derivatives with alloxazine π-conjugated core [42]. It was shown that expansion of the π-conjugated system provided tunable light absorption reaching up to 700 nm.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are a number of erroneous literature reports claiming that the bis-oxime of benzil can be formed under these conditions. [17][18][19] Both syn and anti isomers of benzil derivative 10 have been claimed as they can be separated and the anti isomers form metal-ion complexes. 16 We found that compounds 9 and 10 were both sulfonated with either 4-methylbenzenesulfonyl chloride or propylsulfonyl chloride to give compounds 11-14 which are potential photoacid generators ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%